2020
DOI: 10.1128/mbio.00166-20
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Rhoptry Protein RhopH3 Is Critical for Host Cell Invasion by the Malaria Parasite

Abstract: Merozoites formed after asexual division of the malaria parasite invade the host red blood cells (RBCs), which is critical for initiating malaria infection. The process of invasion involves specialized organelles like micronemes and rhoptries that discharge key proteins involved in interaction with host RBC receptors. RhopH complex comprises at least three proteins, which include RhopH3. RhopH3 is critical for the process of red blood cell (RBC) invasion as well as intraerythrocytic development of human malari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Our structure similarity searches found that RhopH3 residues 434–665 align with domains 2 and 3 of SepL; because domain three mediates interaction with the Tir receptor ( Burkinshaw et al, 2015 ), one possibility is that RhopH3 interacts with an unidentified host cell receptor at this site. The RhopH3 C-terminus provides another surface for the presumed interactions, as suggested by site-directed mutagenesis of serine 804 and by studies with a monoclonal antibody against a 134 aa recombinant fragment ( Doury et al, 1994 ; Ekka et al, 2020 ). This entire region (residues 716–897) is not resolved in our structure and appears to be flexible.…”
Section: Discussionmentioning
confidence: 99%
“…Our structure similarity searches found that RhopH3 residues 434–665 align with domains 2 and 3 of SepL; because domain three mediates interaction with the Tir receptor ( Burkinshaw et al, 2015 ), one possibility is that RhopH3 interacts with an unidentified host cell receptor at this site. The RhopH3 C-terminus provides another surface for the presumed interactions, as suggested by site-directed mutagenesis of serine 804 and by studies with a monoclonal antibody against a 134 aa recombinant fragment ( Doury et al, 1994 ; Ekka et al, 2020 ). This entire region (residues 716–897) is not resolved in our structure and appears to be flexible.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has shown that global phosphorylation of P. falciparum proteome governs many cellular processes including invasion ( Ekka et al., 2020 ; More et al., 2020 ; Perrin et al., 2020 ). In addition, there are scanty findings available that also suggest that global palmitoylation of glideosome-actinomycin motor assembly proteins in P. falciparum might impact the invasion phenotypes ( Jones et al., 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, cross talk between CDPK1 and Protein Kinase A plays a critical role during the invasion process [65] . A recent study has demonstrated that phosphorylation of RhopH3 is critical for invasion of RBCs, correct localization in rhoptries and discharge during invasion [33] . It has been suggested that phosphorylation of RhopH3 is mediated by CDPK1 [33] .…”
Section: Cdpks and Asexual Intra-erythrocytic Development Of Malaria Parasitementioning
confidence: 99%
“…A recent study has demonstrated that phosphorylation of RhopH3 is critical for invasion of RBCs, correct localization in rhoptries and discharge during invasion [33] . It has been suggested that phosphorylation of RhopH3 is mediated by CDPK1 [33] . A recent elegant study by More et al, demonstrates formation of a multimeric complex in merozoites involving phosphorylated CDPK1, regulatory subunit of PKA (PKAr) and Pf14-3-3I that plays a critical role in the invasion process and microneme discharge [79] .…”
Section: Cdpks and Asexual Intra-erythrocytic Development Of Malaria Parasitementioning
confidence: 99%
See 1 more Smart Citation